Intercropping summer moong (Vigna radiata) in turmeric (Curcuma longa L.) -a feasibility study at Punjab - P K Sraw, B Kaur, (Journal of Spices and Aromatic Crops, 2019)
On farm trial on the effect of intercropping of summer moong (Vigna radiata) on growth, yield, and economics of turmeric (Curcuma longa L.) was conducted at farmer’s fields in adopted villages of Krishi Vigyan Kendra viz., Kandola Kalan, Kaimwala, Mehsampur and Fatehpur in Jalandhar district during 2012 and 2013. The experiment was laid out in randomized complete block design with nine treatments. The treatments were T1 - sole turmeric flat (30 cm x 20 cm), T2 - sole turmeric ridge (45 x 15 cm), T3 - sole turmeric ridge (60 x 10 cm), T4 - sole turmeric bed (67.5 cm), T5 - turmeric : summer moong (1:1) flat, T6 -turmeric : summer moong (1:1) ridge 45 x 20 cm, T7 - turmeric :summer moong (1:1) ridge 60 x 20 cm, T8 -turmeric : summer moong (2:1) bed 67.5 cm and T9 - turmeric : summer moong (2:2) bed 67.5 cm. In intercropping treatments, the planting of turmeric was done on the top of ridge and bed and summer moong was sown in furrows. The data on emergence count (30 and 60 DAS), plant height, tillers plant-1 (No.), dry matter accumulation, number of rhizomes (mother, primary, secondary), total rhizomes plant-1, rhizome yield (q ha-1) (fresh, dry and processed) were recorded. The treatments T8 and T9 where turmeric was planted on bed with summer moong in the furrow were found to be better for all the characters under study. The highest net returns of Rs 2.27 x 105 ha-1 with B : C ratio 4.89 was obtained in T9 -turmeric : summer moong (2:2) bed 67.5 cm followed by T8 -turmeric : summer moong (2:1) bed 67.5 cm and recorded lowest net returns of Rs 1.58 x 105 ha-1 with benefit: cost ratio 3.51 in T5 - turmeric : summer moong (1:1) flat. The study revealed that summer moong can be a better option as intercrop in turmeric than the sole turmeric crop for proper utilization of all resources.